Bitter melon (Momordica charantia): a natural healthy vegetable. Issue 1 (1st January 2018) - Saeed, Farhan; Afzaal, Muhammad; Niaz, Bushra; Arshad, Muhammad Umair; Tufail, Tabussam; Hussain, Muhammad Bilal; Javed, Ahsan
ABSTRACT: Bitter melon provides health benefits against various ailments for improving the quality of life. It is nutrient dense plant-based food containing versatility of bioactive compounds such as alkaloids, polypeptide, vitamins, and minerals. Owing to presence of bioactive compounds, it has the ability to fight against various lifestyle related disorders, e.g. cancer insurgence, diabetes mellitus, abdominal pain, kidney (stone), fever, and scabies. Amongst bioactive moieties, p-insulin is similar to insulin whose subcutaneous injection significantly lower blood glucose levels in diabetic patients. It also contains steroidal saponins called charantin, act alike peptides and certain alkaloids that effectively control sugar level in blood. The therapeutic perspectives have been also highlighted as they are helpful in regulating blood cholesterol thus protecting the body from cardiovascular disorders like atherosclerosis. Whole fruit, seeds and leaves of bitter melon regulates impaired antioxidant status and suppress fat accumulation. Moreover, curative potential of its bioactive components and their utilization in value added food products are also the limelight of article.